The Implementation of Think-Talk-Write Learning Model on Teaching Writing for Vocational High School Students - Haryono, Purwo Haryono; Setyandari, Ana; Na’im, Hami (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
Writing is an essential skill in English language learning, especially for vocational high school students who need to develop their communicative competence for professional settings. However, many students face difficulties in organizing their ideas, structuring sentences, and maintaining coherence in their writing. This study aims to investigate the implementation of the Think-Talk-Write (TTW) learning model in teaching writing. Data were collected through classroom observations, interview, and documentation. The findings indicate that the TTW model significantly enhances students’ writing abilities by encouraging critical thinking, collaborative discussions, and structured writing practices. Their writing competence increases from 76.86 to 84.61. Moreover, students demonstrated increased motivation and engagement in the writing process. The study concludes that the TTW model is an effective pedagogical approach for teaching writing in vocational high schools, providing a structured yet flexible framework that fosters students’ cognitive and linguistic development.